Aqua balls effect on solar still productivity using water blended (Nexo Revista Científica, 2023)
With the use of filter ball, the performance regarding the rowing motor solar still is examined. The belt is rotated by a DC motor (6W) that is powered through a small photovoltaic (PV) system. Also, research is done on how employing porous media affects the rowing filter still's performance. The best rowing filter performance, without or with porous media, was found to be achieved at the 30-minute OFF time, according to the results. Additionally, the rowing filter ball in solar still produced 183% more in total compared to standard distiller did. Tow rowing shafts in solar still: New mechanism of desalination Absorbent materials in the stills increase water absorption, and absorb heat when exposed to solar radiation. These materials serve as heat storage media and increase the wetted surface area. The water yield for CSS is improved by 188% when the AQUA balls balls are agitated within the water in the still basin.